Impact of household financing on bank and economic performances in Malaysia - Tunde, Ajani Ibrahim (2020)
Household financing and loans have been increasing in Malaysian banks over the years. Commercial and Islamic banks have relied on this sector to meet up with their profitability and the trend also gives impact on Malaysian economic performance. This study aims to investigate the impact of household financing on bank as well as economic performances. For banks performance, household financing, banks specific variables and macro-economic variables will be regressed on return on asset (ROA) and net profit margin (NPM) of Islamic banks or net interest margin (NIM) of conventional banks. While for economic performance, same variables were deployed on gross domestic product (GDP) and money supply for the period between 2004 and 2018. The results revealed that household financing has a positive impact on Islamic bank ROA and negative impact on NPM, while conventional banks show a positive impact to both ROA and NIM. The results also show that household financing/loan have negative relationship with economic performance. There is an increasing direction stating a higher household loan or financing could deteriorate economic performance. The result gives signal to household indebtedness which it could has adverse effect on the economy at large.